Fabrication of Nanoreaction Clusters with Dual‐Functionalized Protein Cage Nanobuilding Blocks. Issue 35 (31st July 2018) - Choi, Hyukjun; Choi, Bongseo; Kim, Gwang Joong; Kim, Han‐ul; Kim, Hansol; Jung, Hyun Suk; Kang, Sebyung
Abstract: Fabrication of functional nanostructures is a prominent issue in nanotechnology, because they often exhibit unique properties that are different from the individual building blocks. Protein cage nanoparticles are attractive nanobuilding blocks for constructing nanostructures due to their well‐defined symmetric spherical structures, polyvalent nature, and functional plasticity. Here, a lumazine synthase protein cage nanoparticle is genetically modified to be used as a template to generate functional nanobuilding blocks and covalently display enzymes (β‐lactamase) and protein ligands (FKBP12/FRB) on its surface, making dual‐functional nanobuilding blocks. Nanoreaction clusters are subsequently created by ligand‐mediated alternate deposition of two complementary building blocks using layer‐by‐layer (LbL) assemblies. 3D nanoreaction clusters provide enhanced enzymatic activity compared with monolayered building block arrays. The approaches described here may provide new opportunities for fabricating functional nanostructures and nanoreaction clusters, leading to the development of new protein nanoparticle‐based nanostructured biosensor devices. Abstract : Nanoreaction clusters constructed from dual‐functionalized protein cage building blocks are prepared by ligating both binding ligands and enzymes on a single Aquifex aeolicus through the bacterial superglue system. The multilayered configuration exhibits superior enzymatic activity to that of monolayered 2D arrays.